The Influence of Motivation and Work Environment on Employee Performance at the Environmental Service Office of Serang City, Banten - Dedi Daryanto (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2020)
This study aims to determine the effect of motivation and work environment on employee performance at the Environmental Service Office in Serang City, Banten. The method used is explanatory research with analytical techniques using statistical analysis with regression, correlation, determination and hypothesis testing. The results of this study motivation significantly influence employee performance by 47.8%, hypothesis testing obtained t count > t table or (7,774 > 1,997). The work environment has a significant effect on employee performance by 42.6%, hypothesis testing is obtained t count > t table or (7.003 > 1.997). Motivation and work environment simultaneously have a significant effect on employee performance with the regression equation Y = 7.927 + 0.439X1 + 0.371X2, and the contribution of the influence is 58.3%, hypothesis testing is obtained F count > F table or (45.379 > 2,750).